ANALISIS PENERAPAN 5 C DALAM PEMBERIAN KREDIT KONSUMTIF PADA PT. ADIRA DINAMIKA MULTIFINANCE CABANG NANGKA PEKANBARU - Alex Yulianto; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The problem in this research is the existence of bad debts, while PT. Adira Dinamika Multi Finance Branch Nangka Pekanbaru is already implementing 5C analysis is an analysis of the character, capacity, capital, collateral, and the condition of economic. This study aims to identify and analyze Implementation 5C In Consumer Lending At PT. Adira Dinamika Multi Finance Branch Nangka Pekanbaru. The study concluded the application of 5C In Consumer Lending At PT. Adira Dinamika Multi Finance Branch Nangka Pekanbaru rated running is good enough. Only in the supervision on the ground for the implementation of character analysis is still lacking, resulting in frequent falsification of the data of borrowers. Based on interviews with informants showed that the character analysis on PT. Adira Dinamika Multi Finance Branch Nangka Pekanbaru is an analysis of the most important compared with other analyzes. Dimensional analysis of other aspects are also important but if the nature of a prospective customer is not good, it will have a negative impact on other dimensions of analysis for dimensional analysis of the application of this 5C intertwined with each other.Keywords: character, capacity, capital, collateral, condition of economic